EXAMINING THE HISPANIC PARADOX IN C-REACTIVE PROTEIN (CRP) IN MIDDLE-AGED AND OLDER AMERICANS - Armendariz, M. (Innov Aging, 2017)
Although the Hispanic Paradox indicates that Hispanics’ health is comparable to non-Hispanic Whites, empirical data suggest this paradox may not exist in biological health profiles. This study examines the Hispanic Paradox in C-reactive protein (CRP), a biological indicator of inflammation. Data were pooled from the 2006 and 2008 core and biomarker waves of the Health and Retirement Study, a nationally representative study of middle-aged and older Americans. Multiple regression analyses tested the relationship between adults of Mexican origin (n = 727) and CRP, net of the effects of immigrant status and survey language preference. Mexican Americans had higher CRP levels than Whites, controlling for age and sex (β=.06, p<.01); however, when both immigration status and language preference were controlled, the association between being Mexican American and CRP was reduced to non-significance (β=.04, p>.05). Future research should fully investigate how biological, social and behavioral factors link Mexican origin to higher CRP.